Insuficiência funcional e lipidose hepática em ovinos: protocolo para indução experimental - Rossi, Carlos Augusto Rigon (2002)
Fatty liver in cattle, develops from excessive mobilization of body fat and the limited hepatic ability to export triglyceride-containing lipoproteins. The objective of the present work was to induce hepatic insufficiency followed by liver fat accumulation in sheep with isopropanol. The dose used was 3g/kg PO after 24 hours fast. Liver fragments collected from biopsy were imersed in NaCl solutions of different concentrations and their fluctuation observed. The animals were subjected to 5 blood samples and liver tissue (biopsy). Sampling, collected at 8-hour intervals, for 32 and 24 hours, respectively. As compared to hour 0, biopsia from other periods in a solution with a lower NaCl concentration, indicating fat accumulation. Serum cholesterol levels showed no differences between hour 0 and the other periods. Serum glucose levels showed a reduction at 8 and 16 hours followed by recovery. Serum triglycerides levels showed a decrease between at 16, 24 e 32 hours, as compared to time 0. The AST levels showed an increase between at hours 16, 24 e 32. Blood urea levels were increased in all periods when compared to hour 0. In the other hand, control values were unaltered. In conclusion, the increase in blood levels of AST and urea; the reduction in triglycerides indicate the isopropanol is efficient in inducing a reversible functional hepatic insufficiency. Moreover, the reduction in NaCl concentration needed to fluctuate liver fragments allied to the visual aspect of liver and samples suggest that insufficienty is also accompanied by fat deposition.